2016
DOI: 10.1002/cssc.201600333
|View full text |Cite
|
Sign up to set email alerts
|

Stable Deep Doping of Vapor‐Phase Polymerized Poly(3,4‐ethylenedioxythiophene)/Ionic Liquid Supercapacitors

Abstract: Liquid-solution polymerization and vapor-phase polymerization (VPP) have been used to manufacture a series of chloride- and tosylate-doped poly(3,4-ethylenedioxythiophene) (PEDOT) carbon paper electrodes. The electrochemistry, specific capacitance, and specific charge were determined for single electrodes in 1-ethyl-3-methylimidazolium dicyanamide (emim dca) ionic liquid electrolyte. VPP-PEDOT exhibits outstanding properties with a specific capacitance higher than 300 F g(-1) , the highest value reported for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 66 publications
(79 reference statements)
2
44
1
Order By: Relevance
“…In part this is due to the PhenylPO4 not doping to the same level as Tos – (1 anion in 2.4 EDOTs vs. 1 in 1.8), as shown in Figure (c) (determined from XPS, see Supporting Information Figure S2). It is important to note that the very high doping level herein compared with that generally reported as the theoretical limit for PEDOT (1 anion in 3 EDOTs) is hypothesised to be related to coordination of anions with the triblock copolymer within the VPP PEDOT . In direct comparison with PhenylPO42, the insertion of Cl – yields a similar doping level to PhenylPO42 but a conductivity 2.5 times higher.…”
Section: Resultsmentioning
confidence: 49%
See 2 more Smart Citations
“…In part this is due to the PhenylPO4 not doping to the same level as Tos – (1 anion in 2.4 EDOTs vs. 1 in 1.8), as shown in Figure (c) (determined from XPS, see Supporting Information Figure S2). It is important to note that the very high doping level herein compared with that generally reported as the theoretical limit for PEDOT (1 anion in 3 EDOTs) is hypothesised to be related to coordination of anions with the triblock copolymer within the VPP PEDOT . In direct comparison with PhenylPO42, the insertion of Cl – yields a similar doping level to PhenylPO42 but a conductivity 2.5 times higher.…”
Section: Resultsmentioning
confidence: 49%
“…In more detailed studies by Bubnova et al, the differences from the use of PSS – or Tos – were shown to arise from a transition in the conducting polymer from a Fermi glass to a semimetal respectively. Despite the demonstration of PEDOT in electrical applications from thermoelectronics to spintronics to energy storage, no rationale has been provided to explain the role of the doping anion in achieving high electrical conductivity. Notably theoretical modelling, that is an essential and standard tool in many fields of material science, is to a large extend missing in conducting polymer research where the interpretation of experiments seldom relies on theoretical calculations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] Although PEDOT:PSS is the most researched form of PEDOT, many other counterions, such as chloride and p-toluenesulfonic acid (tosylate or Tos), have been investigated. [7] The choice of counter ion affects the doping level as well as the packing of the PEDOT chains and thus influences the conductivity. PEDOT:PSS can reach conductivities of ~1000 S/cm, while values of 2000-5000 S/cm have been reported with counterions such as tosylate [8] or trifluoromethanesulfonate [9] .…”
Section: Pedotmentioning
confidence: 99%
“…Typical reported values of capacitance based on conductive polymers is in the range 10-200 F/g. [7,39,102] Some metal oxides, like ruthenium oxide, have superior capacitance compared to both carbon and conductive polymers with a specific capacitance ~1000 F/g. [99] However, they often suffer from low conductivity and poor ion permeability.…”
Section: Supercapacitorsmentioning
confidence: 99%